PELATIHAN PENGOLAHAN SAMPAH PLASTIK RESIDU MENJADI BAHAN PAVING BLOK - Sujono, Sujono; Musafa, Akhmad; Purnawan, Peby Wahyu; Budi, Agus Setya; Susilowati, Tutik Sri (Universitas Budi Luhur, 2024)
Residual plastic is part of plastic waste that has no economic value and has the potential to pollute the environment. One of the utilization of residual plastic is pyrolysis technology to produce fuel. However, pyrolysis is economically unfavorable and the technology is complicated. In this community service activity, collaboration with Bank Sampah Budi Luhur has been carried out in making a residual plastic processing tool with a capacity of 5 liters, cheap, practical, and easily understood by ordinary people. The purpose of this activity is to create a tool for utilizing residual plastic. The tool made has been tested in the process of making paving block product samples. Laboratory tests of the samples were carried out and obtained strength against compressive force reached 33.5 kg/cm2 for the composition of materials consisting of used oil, chopped residual plastic, and sand in a ratio of 1:1:0.5. Socialization of the operation of residual plastic waste processing tools was carried out to residents of Employee 3, Karang Tengah Kel, Kec. Ciledug, Tangerang, which is a partner of the Waste Bank of Budi Luhur University. The evaluation of the activity showed that the community gained insight into residual plastic waste processing tools so that they were more useful and able to reduce the rate of environmental pollution.